A dinâmica espacial da microrregião de Cajazeiras no período de 1980 até a primeira década de 2000 - COSTA, Alberson Silva (2014)
The research has now held as an object of analysis Microrregião Cajazeiras and aims to take your Space Dynamics. The procedures used for research ranging from bibliographic queries to the Case Study, which has the sample universe of 300 interviews, which equates to 10% of the entrepreneurial ventures Microrregião. The research was developed initially with the light approaches the Space Economy and urban issues by claiming to theoretically support the local dynamics of Microrregião then were placed conditions insertion of Salvador in Bahia and economic context of the metropolitan region in order justify by means of immigration the Urban problems. In this scenario, the housing problems were raised and consequentimente the motivations of the emergence of housing developments Cajazeiras. Thus, the research enabled a lesser extent, to evaluate not only the urban problems of the micro-region, but the entrepreneur of his people and even their spatial behavior contrasts. Although the present Microrregião Cajazeiras lowest population density in relation to other districts that make up the urban core of Salvador, its population growth impacts generated that changed the landscape, especially with the appearance of cozy spaces of irregular housing and saturation of existing infrastructure generating, however, a process of casualization of space, which hinders its development.